Coups de pieds en talons hauts : politiques du corps et performancescapes dans les scènes drag et ballroom grecques contemporaines - Natalia Koutsougera; Amalia Maria Kontou (Genre, Sexualité et Société)
In the last few years, after the economical crisis of 2008, homophobic violence, transphobia and femmephobia intensified in Greece. Simultaneously, new mediaesthetics, hyperpolitical imperatives and visualities emerged and redefined the queer and drag artistry. These constructed realities draw on an almost postmodernist, post-ironic take on of Greek pop culture, beauty standards and politics. Drawing on local and international influences, the Greek drag and ballroom movements artistically subvert the audience expectations with “alternative and chaotic imaginings of gender” (Davies, 2012) and new self-referential pop cultural references that “highlight the fakeness of the natural” (Van de Port, 2012). Very often these appropriations are read as “in war with Greekness” (Ieropoulos, 2018) and embody the archetype of the modern “deviant” and blaspheme in the eyes of the conservative Christian Orthodox Greek society. In a similar vein, modern voguers dress up in awkward costumes, which distort images of extravagant pop femininity, to publicly perform combative and excessive dips in high heels. In this respect, this paper proposes an exploratory analysis of the mischievous and dubious performances of the drag and ballroom scenes in Athens. In so doing, we unveil the political configurations and performative rhizomes that reach beyond inter-communal and extra-communal interpretations and imageries of resistance.